2012
DOI: 10.3892/etm.2012.868
|View full text |Cite|
|
Sign up to set email alerts
|

The correlation between microvessel pathological changes of the endplate and degeneration of the intervertebral disc in diabetic rats

Abstract: In this study, the pathological microvessel changes to the endplate and the degeneration of the intervertebral disc of diabetic rats were examined in order to identify the possible mechanism by which diabetes mellitus (DM) induces degeneration of the intervertebral disc. A total of 30 Sprague-Dawley rats were randomly divided into two groups. DM was induced in one of the groups by streptozotocin (STZ) administration. The rats were sacrificed 4, 8 and 12 weeks later. Five rats from each group were sacrificed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…We identified 9511 published studies related to the issue IVDD. Out of these 27 manuscripts were related to the topic IVDD in diabetic rodent models, which is our research field of interest [ 3 , 15 , 43 , 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], see Table 4 and Table 5 . By further evaluation another four publications were excluded; two of them discussed the diabetic animal models used in IVDD, including rodents, but they were not related to IVDD.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 9511 published studies related to the issue IVDD. Out of these 27 manuscripts were related to the topic IVDD in diabetic rodent models, which is our research field of interest [ 3 , 15 , 43 , 47 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], see Table 4 and Table 5 . By further evaluation another four publications were excluded; two of them discussed the diabetic animal models used in IVDD, including rodents, but they were not related to IVDD.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies assumed that hyperglycemia enhances the formation of advanced glycation end products (AGEs) in the NP which leads to the progression of disc degeneration [ 4 , 18 , 19 ]. Chen et al [ 20 ] found that DM accelerated the degeneration process of the disc by microangiopathy. Autophagy of the nucleus pulposus and annulus fibrosis cells also appears to play an important role in LDD [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetik yatkınlık, aile hikayesi, yaş sigara kullanımı gibi risk faktörleri-nin yanında diabetin de mikroanjiopati yaparak LDH'ya yol açabileceği belirtilmiştir [22,24]. Chen ve arkadaşlarının [25] yaptığı çalışmada kan şeke-ri yüksekliği ve düşük oksijenlenmenin sonucunda oluşan glikolizasyon son ürünlerinin mikrodamar sayısında azalma veya tıkanmaya yol açabileceği bunun sonucunda da disk endplatelerinin mikrovasküler endotelyal hücre yaralanmasına neden olabileceği bildirilmiştir. Mekanik özellikleri bozulan diskte travmalara açık hale gelir.…”
Section: Discussionunclassified